Ultrafast magnetization and structural dynamics in the intercalated transition metal dichalcogenides Fe0.25TaS2 and Mn0.25TaS2. (20th April 2016) - Liu, Q; Zhu, X D; Wang, L H; Cheong, S-W; Tobey, R I
Abstract: We measure magnetization and structural dynamics in two intercalant-ordered transition metal dichalcogenides: Fe0.25 TaS2 and Mn0.25 TaS2 . The structurally equivalent materials allow us to probe the effect of orbital angular momentum which is active in Fe0.25 TaS2 and absent in Mn0.25 TaS2 . Interestingly, we find that the magnetooptics dynamics are nearly indistinguishable in these two materials, in contradiction to conventional explanations of a spin–lattice mechanism. We compare our results to other materials where spin–lattice demagnetization has been put forth as a demagnetization channel.